2020
DOI: 10.3389/fneur.2020.00642
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Observation of Low-Dose Rituximab Treatment in Chinese Patients With Neuromyelitis Optica Spectrum Disorders in a Real-World Setting

Abstract: Objective: This study aimed to investigate the efficacy and safety of low-dose rituximab (RTX) in the treatment of neuromyelitis optica spectrum disorders (NMOSD) patients. Methods: NMOSD patients were treated with RTX at ~25% of the standard dose. The annualized relapse rate (ARR), expanded disability status scale (EDSS) score, visual function system scale (VFSS) and length of spinal cord lesions before and after treatment were statistically compared. The dynamic changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…1), which was consistent with previous studies [16, 17]. However, previous studies on CD19 + B cells focused on the changes before and after RTX treatment, and they aimed to maintain the percentage of CD19 + B cells <1% [16, 17]. In our research, the current disease duration for acute NMOSD was 7 days (IQR = 10.5) and that for chronic NMOSD was 120 days (IQR = 157.5).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1), which was consistent with previous studies [16, 17]. However, previous studies on CD19 + B cells focused on the changes before and after RTX treatment, and they aimed to maintain the percentage of CD19 + B cells <1% [16, 17]. In our research, the current disease duration for acute NMOSD was 7 days (IQR = 10.5) and that for chronic NMOSD was 120 days (IQR = 157.5).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that the levels of peripheral blood CD19 + B cells were significantly higher in patients with acute NMOSD and remission NMOSD than in HCs (17.91 ± 8.7%, 13.08 ± 7.562%, and 12.48 ± 3.575%, respectively; p < 0.001) (Table 2; Fig. 1), which was consistent with previous studies [16, 17]. However, previous studies on CD19 + B cells focused on the changes before and after RTX treatment, and they aimed to maintain the percentage of CD19 + B cells <1% [16, 17].…”
Section: Discussionsupporting
confidence: 92%
“…The capability of the immune system to resist viral infection is based on the humoral response mediated by B-cells. Some studies have shown B-cell inhibitors such as rituximab and azathioprine are often used as a long-term treatment method for the patients with NMOSD (11)(12)(13)(14), which could reduce concentrations of immunoglobulins G and M and increase the risk of COVID-19 infection (9,15). Therefore, patients who developed iatrogenic lymphopenia should be advised to maintain social distancing even in areas where lockdown has been removed or ameliorated (16).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous reports have shown that patients with autoimmune diseases, especially in the Chinese cohort, including anti-NF155 autoimmune nodopathies, MG, NMOSD, and Isaacs syndrome, responded very well to the low-dose rituximab regimen (10,(46)(47)(48)(49). This low-dose regimen could also lead to improvement of clinical manifestations, such as manual muscle testing and diseaserelated scales, decrease in antibody titers, and reduction of average steroid dosage by B cell elimination and subsequent B cell repopulation.…”
Section: Discussionmentioning
confidence: 92%